CuI Nanoparticle‐Catalyzed Regioselective Synthesis of 3‐Nitro‐2‐arylimidazo[1, 2‐a]pyridines using Oxygen as Oxidant. Issue 3 (21st February 2022) - Das, Dibya; Jena, Ashis Kumar; Pal, Chandan Kumar; Bourda, Laurens; Van Hecke, Kristof
Abstract: A mild, efficient and stable copper iodide nanoparticle (CuI NP)‐catalyzed regioselective synthesis of 3‐nitro‐2‐arylimidazo[1, 2‐ a ]pyridines was developed. Substituted 2‐amino pyridines successfully reacted with both electron‐rich and electron‐deficient β‐nitro styrenes to produce the desired products in good to excellent yields. Hot filtration tests confirmed the heterogeneous nature of the CuI NPs. The nanocatalyst showed good reusability up to three consecutive cycles without any significant loss in its activity and product yield, confirmed by high‐resolution transmission electron microscopy (HR‐TEM) analysis. Use of molecular oxygen as oxidant is advantageous from an economic and environmental point of view. Abstract : A copper iodide nanoparticle‐catalyzed synthesis of 3‐nitro‐2‐arylimidazo[1, 2‐ a] pyridines has been developed under oxygen atmosphere. The reaction exhibited a high level of regioselectivity with moderate to excellent yield.